Rainfall on the Greenland Ice Sheet: Present‐Day Climatology From a High‐Resolution Non‐Hydrostatic Polar Regional Climate Model. Issue 15 (27th July 2021) - Niwano, M.; Box, J. E.; Wehrlé, A.; Vandecrux, B.; Colgan, W. T.; Cappelen, J.
Abstract: Greenland ice sheet rainfall is expected to increase under a warming climate. Yet, there have been no active long‐term in‐situ rainfall records on the ice sheet due to observational difficulties. Here, we utilize the state‐of‐the‐art 5 km polar non‐hydrostatic regional climate model NHM‐SMAP to evaluate the ice sheet's rainfall over 40 years (1980–2019). The largest trends include a fourfold increase in annual rainfall for the northwestern ice sheet; 3.1 Gt year −1 or 12 mm m −2 year −1 . September ice‐sheet‐wide rainfall amount and intensity increase by 7.5 Gt month −1 and 20.8 mm h −1 year −1 . In the last two decades, the increasing September maximum hourly rainfall rate exceeded 50 mm h −1 six times. The increased surface water delivery has numerous implications, including for snow metamorphism and ice flow dynamics. Plain Language Summary: We find that rainfall has increased over the Greenland ice sheet from 1980 to 2019. Among the eight major ice‐sheet drainage areas, the northwestern sector stands out as an increasing rainfall hotspot where the annual rainfall has increased fourfold. For the entire ice sheet, September's total rainfall and its intensity increased by 224% and 54% above the 1981–2010 baseline over the last 40 years. An increase in late melt season rainfall is expected to contribute to an increase in late summer snow and ice melt. Our results provide the first detailed quantification of the state of ice sheet rainfall climatology. Key Points: A 5 km horizontal resolution non‐hydrostatic regional climate model is used to evaluate Greenland ice sheet rainfall from 1980 to 2019 The northwestern sector stands out as a hotspot of increasing rainfall Both the amount and intensity of September ice‐sheet‐wide rainfall have significantly increased in the 40 years from 1980 to 2019